2007
DOI: 10.1016/j.chom.2007.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Pathogen-Induced Necrotic Cell Death Mediated by the Inflammasome Components CIAS1/Cryopyrin/NLRP3 and ASC

Abstract: Cryopyrin (CIAS1, NLRP3) and ASC are components of the inflammasome, a multiprotein complex required for caspase-1 activation and cytokine IL-1beta production. CIAS1 mutations underlie autoinflammation characterized by excessive IL-1beta secretion. Disease-associated cryopyrin also causes a program of necrosis-like cell death in macrophages, the mechanistic details of which are unknown. We find that patient monocytes carrying disease-associated CIAS1 mutations exhibit excessive necrosis-like death by a process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
273
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(297 citation statements)
references
References 63 publications
18
273
2
4
Order By: Relevance
“…In the case of Shigella, the bacteria rapidly induce macrophage cell death at early stages of infection, which is accompanied by NLR inflammasome activation and inflammatory cell death through a T3SS-dependent mechanism (19,22). Previous studies indicated that during replication in macrophages, LPS, peptidoglycan, and T3SS rod or needle components of Shigella are recognized by the NLRC4 and NLRP3 inflammasomes (8,(19)(20)(21). Interestingly, the mode through which NLRs recognize Shigella infections seems to vary across different infection conditions.…”
Section: Significancementioning
confidence: 99%
“…In the case of Shigella, the bacteria rapidly induce macrophage cell death at early stages of infection, which is accompanied by NLR inflammasome activation and inflammatory cell death through a T3SS-dependent mechanism (19,22). Previous studies indicated that during replication in macrophages, LPS, peptidoglycan, and T3SS rod or needle components of Shigella are recognized by the NLRC4 and NLRP3 inflammasomes (8,(19)(20)(21). Interestingly, the mode through which NLRs recognize Shigella infections seems to vary across different infection conditions.…”
Section: Significancementioning
confidence: 99%
“…90 However, at higher MOI, Shigella induces a caspase-1-independent form of cell death termed pyronecrosis. 104 Diseaseassociated cryopyrin appears to trigger this death mode as well, which is independent of caspase-1 but presumably requires cathepsin B. 104 The IPAF-caspase-1 inflammasome has been recently shown to be essential for the initiation of a proper innate immune response to Pseudomonas aeruginosa.…”
Section: Caspase-independent Cell Death: Oncosis and Pyronecrosismentioning
confidence: 99%
“…104 Diseaseassociated cryopyrin appears to trigger this death mode as well, which is independent of caspase-1 but presumably requires cathepsin B. 104 The IPAF-caspase-1 inflammasome has been recently shown to be essential for the initiation of a proper innate immune response to Pseudomonas aeruginosa. 51,91 Virulent P. aeruginosa isolates that evade the immune response express the effector protein exoenzyme U (ExoU).…”
Section: Caspase-independent Cell Death: Oncosis and Pyronecrosismentioning
confidence: 99%
“…Also in these cases, inhibition of cathepsin B, and possibly other proteases, by CA-074-Me attenuated cell death and limited inflammatory cytokine release (Willingham et al, 2007;Duncan et al, 2009). This further suggests that inducers of pyrogenic cell death, including lysosome-destabilizing agents, trigger different cellular events, which importantly rely on the extent and timing of LMP.…”
Section: Pyroptosismentioning
confidence: 99%